Observasi dan identifikasi Penyakit Jamur Akar pada Tanaman Pala di Kabupaten Aceh Selatan - Rita Harni; Iwa Mara Trisawa; Agus Wahyudi (Jurnal Tanaman Industri dan Penyegar, 2011)
Nutmeg has important role to the national economiy because of export of the product. White root disease is the main constraint in nutmeg production. The objective of this research was observation and identification of the attack and intensity causes respectively. The research conducted in April to July 2011 on farmer’s farm and on phytopathology laboratory of Indonesian Spices and Industrial Crops Research Institute Sukabumi. Survey has been done in five sub-districts namely, Tapak Tuan (Air Berudang and Air Pinang village), Sawang (Simpang Tiga and Lhok Pawoh), Meukek (Alue Meutuah dan Blang Kuala), Labuan Haji Timur (Gunung Rotan dan Keumumu Hilir), and Kluet Utara (Gunung Pulo dan Krueng Batu). Observation was done on persentage of attacks, symptoms of pests and diseases, and soil condition. The samples were taken from the root, stem and soil then isolated and identified conventionaly and molecularly in laboratory. The results showed that cause of the death of nutmeg plant was white root fungus caused by Rigidoporus microporus with attcak intensity from 5% to 100%.